Revealing Underlying Processes Involved in Light Soaking Effects and Hysteresis Phenomena in Perovskite Solar Cells. Issue 14 (15th May 2015) - Zhao, Chen; Chen, Bingbing; Qiao, Xianfeng; Luan, Lin; Lu, Kai; Hu, Bin
<x xml:space="preserve">Abstract</x> Light soaking and hysteresis phenomena can reveal the bulk and interfacial polarization effects on photovoltaic processes in perovskite solar cells. The frequency‐dependent impedance and time‐dependent photoluminescence measurements indicate that bulk and interfacial polarizations are internally coupled in developing short‐circuit current, open‐circuit voltage, and fill factor through charge dissociation, transport, and collection in light soaking and hysteresis phenomena.